Perceived Stress in Obsessive–Compulsive Disorder is Related with Obsessive but Not Compulsive Symptoms - Morgado, Pedro; Freitas, Daniela; Bessa, João M.; Sousa, Nuno; Cerqueira, João J. (Frontiers in Psychiatry, 2013)
Obsessive-compulsive disorder (OCD) is a chronic psychiatric disorder characterized by recurrent intrusive thoughts and/or repetitive compulsory behaviors. This psychiatric disorder is known to be stress responsive, as symptoms increase during periods of stress but also because stressful events may precede the onset of OCD. However, only a few and inconsistent reports have been published about the stress perception and the stress response in these patients. Herein, we have characterized the correlations of OCD symptoms with basal serum cortisol levels and scores in a stress perceived questionnaire (PSS-10). The present data reveals that cortisol levels and the stress scores in the PSS-10 were significantly higher in OCD patients that in controls. Moreover, stress levels self-reported by patients using the PSS-10 correlated positively with OCD severity in the Y-BOCS. Interestingly, PSS-10 scores correlated with the obsessive component, but not with the compulsive component, of Y-BOCS. These results confirm that stress is relevant in the context of OCD, particularly for the obsessive symptomatology.